The Role of Bridges in the Shaping of Specific Historical and Cultural Landscapes: A Case Study of Jianchuan, Yunnan - Zhou, Fengyi; Buranaut, Isarachai (Journal of Architectural/Planning Research and Studies (JARS), 2025)
This study is based on first-hand research data and uses the three steps of Open Coding, Axial Coding, and Selective Coding in grounded theory to conduct an in-depth analysis of the bridges in the historical and cultural context of Jianchuan County, Yunnan, China. A theoretical model of cultural landscape interaction in a specific area also is constructed with bridges as the theme. This research aims to gain insights into the functions and forms of different types of bridges, analyze the long-term interaction patterns between people and rivers, reveal the living and production needs of local people, and determine how bridges in the area are integrated, shaped, and continue to influence the local cultural landscape. This study shows that bridges reflect the interaction patterns between local people and rivers driven by basic needs. Bridges also participate deeply in the cultural landscape along the river, shaping it through their connections. During this process, convenient transportation has transformed the landscape. Bridges have become an important carrier for connecting different communities and cultures, enriching historical and cultural landscapes along rivers, and effectively enhancing agricultural landscapes as well as cultural and ecological values. This study provides an understanding of the dynamic evolution of cultural landscapes in the area and establishes theoretical support for the protection and management of cultural heritage, as well as urban planning, to ensure that historical bridges are effectively protected and inherited in the process of modernization, referencing data to optimize future bridge design and urban space layouts.